Success Rate of Contemporary Regenerative Endodontic Therapy and the Expected Outcomes of the Endodontic Microsurgery: A Systematic Review and Meta-Analysis - Golchin Jabbari; Samira Jamali; Navid Nasrabadi; Fereshte Keikha (Association of Support to Oral Health Research (APESB), 2021)
Objective: To examine the level of the accumulating success of the modern Resin-Based Endodontic Surgery (RES) and comparison with Endodontic Microsurgery (EMS) and finally offer a replacement at the predicted final results of EMS. Material and Methods: MEDLINE, PubMed, Cochrane Library, Embase, ISI, Google Scholar have been utilized as electronic databases for systematic literature until 2019. Therefore, Endnote X9, which can be provided in the market, has been applied to manage the electronic titles. Searches have been made with keywords "Endodontic Microsurgery OR EMS ", "Resin-Based Endodontic Surgery OR RES", "Regenerative Endodontic Therapy"," Root-End Filling", "Root-End Surgery", "Periapical Surgery" and "Endodontics". Thus, this systematic review has been conducted concerning the basic investigation of the PRISMA Statement-Preferred Reporting Items designed for the Meta-analyses and Systematic Reviews. Results: A total of RES =19 and EMS =31 with potential pertinent abstracts and topics were discovered in manual and electronic searches. Then, three articles for RES and four studies for EMS publications satisfied our inclusion criteria necessary for systematically reviewing the studies. The analysis showed the success rate for EMS as equal to 1.16 times the probability of the success rate for RES. Conclusion: Micro-surgical procedures superiorly achieved the predictable high success rate for the Root-end surgery compared to conventional methods.